A DC chopper controller for a battery electric vehicle - Claassen, Michael David (Department of Electrical Engineering, 2016)
The battery electric vehicle is presented as a pollution free alternative to the internal combustion engined vehicle as a form of commuter transport in city centres. To conserve battery energy as much as possible, an efficient drive system, consisting of a chopper controller and a permanent magnet motor, is described and tested in four modes of operation - two modes of motoring and two of regenerative braking. From the experimental results, it was estimated that approximately 10% of the energy expended by the vehicle during motoring could be returned to the battery if regenerative braking is employed under stop-start driving conditions. The operation of transistor and thyristor choppers is described, and their suitability for use in a vehicle drive system is discussed. A proposed vehicle control system, incorporating a thyristor array and associated logic for implementing the mode selection, is described and evaluated.